Dynamics Pattern of Urban Population in Sumatera Island (Bandar Lampung City, Palembang City, Bengkulu City in 1980-2020) - Malik, IB Ilham; Noviani, Erina; Yasmiin, Regita Cahyani (Universitas Bandar Lampung (UBL), 2025)
This research aims to analyze the comparison of population growth and density in three large cities in Sumatra, Bandar Lampung City, Palembang City and Bengkulu City, during the 1980-2020 period. The data used in this research includes population censuses, government statistical reports, and other secondary data sources. The analysis was carried out using quantitative descriptive methods, by calculating annual population growth rates and analyzing population density in each census period. The results showed that all three cities experienced significant population growth, with Bandarlampung having the highest growth rate (32.24%), followed by Bengkulu City (17.53%), and Palembang City (14.68%). At the end of the research period, Bandarlampung also had the highest population density (6892 people/km2), while Bengkulu City had the lowest density (2635 people/km2). This research analyzes 40-year population dynamics in three cities with different geographic and economic characteristics. His comparative approach links growth and density, providing a picture of urbanization and infrastructure challenges in Sumatra's large cities. This research recommends adaptive spatial planning in the city of Bandar Lampung as well as equitable development in the city of Palembang and the city of Bengkulu to encourage investment and balanced growth. Improvements in access to clean water, transportation, and health services are needed to support sustainable urbanization.Keywords: Population growth and density; Bandarlampung; Palembang; Bengkulu